2021
DOI: 10.1039/d0se01500h
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of nickel–iron (oxy)hydroxide (NiFeOOH) electrocatalysts on hematite photoanodes

Abstract: A NiFeOOH electrocatalyst prepared by photo-assisted anodic deposition on hematite performs a dual function: increasing the water oxidation kinetics and suppressing surface charge recombination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…As for the ED-hematite, the Ni 25 Fe 75 OOH showed lower OER overpotential than Ni 75 Fe 25 OOH. This is remarkable, given the several reports in the literature on the superior OER performance of Ni 25 Fe 75 OOH. ,, They attributed the lower performance of Ni 75 Fe 25 OOH to the formation of the hematite-NiO x layer at the interface that acts as a recombination center, while Ni 25 Fe 75 OOH effectively collected the photogenerated holes by passivating the hematite surface states. It is important to note here that the Ni 25 Fe 75 OOH consists of two separate phases; a FeOOH phase and a Fe-doped NiOOH phase. , In another study, Kim et al reported a remarkable improvement in the OER performance in BiVO 4 when a FeOOH layer was deposited between the BiVO4 semiconductor and the NiOOH catalyst.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…As for the ED-hematite, the Ni 25 Fe 75 OOH showed lower OER overpotential than Ni 75 Fe 25 OOH. This is remarkable, given the several reports in the literature on the superior OER performance of Ni 25 Fe 75 OOH. ,, They attributed the lower performance of Ni 75 Fe 25 OOH to the formation of the hematite-NiO x layer at the interface that acts as a recombination center, while Ni 25 Fe 75 OOH effectively collected the photogenerated holes by passivating the hematite surface states. It is important to note here that the Ni 25 Fe 75 OOH consists of two separate phases; a FeOOH phase and a Fe-doped NiOOH phase. , In another study, Kim et al reported a remarkable improvement in the OER performance in BiVO 4 when a FeOOH layer was deposited between the BiVO4 semiconductor and the NiOOH catalyst.…”
Section: Resultsmentioning
confidence: 91%
“…This is remarkable, given the several reports in the literature on the superior OER performance of Ni 25 Fe 75 OOH. 11,16,27 They attributed the lower performance of Ni 75 Fe 25 OOH to the formation of the hematite-NiO x layer at the interface that acts as a recombination center, while Ni 25 Fe 75 OOH effectively collected the photogenerated holes by passivating the hematite surface states. It is important to note here that the Ni 25 Fe 75 OOH consists of two separate phases; a FeOOH phase and a Fe-doped NiOOH phase.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar study confirmed that catalytic properties of the deposited layer might not be important for the PEC activity of photoanodes, as surface passivation and hence reduced recombination are the predominant sources of PEC activity improvement [ 38 , 39 , 40 ]. It has also been suggested that a co-catalyst can play both a catalytic role and a non-catalytic one, enhancing not only charge transfer but also the overall stability [ 40 , 41 ], while the predominant effect should be dependent on the nature of the photoelectrode material, the nature of the co-catalyst, as well as on the thickness and uniformity of the co-catalyst layer. It is always problematic to deduce the actual role of the co-catalyst, as one needs to address the competition between charge transfer and electron-hole recombination and understand which of these two factors is altered to a greater extent by the co-catalyst deposition [ 40 ].…”
Section: Introductionmentioning
confidence: 99%